Activity Limitations and Healthcare Access as Correlates of Frequent Mental Distress in Adults 65 Years and Older - Zuzana Segev PhD; Ahmed A. Arif MD, PhD; James E. Rohrer PhD (SAGE Publishing, 2012)
Objectives : Poor mental health is a major source of distress, disability, and social burden in older adults. The objective of this study was to determine if activity limitation and healthcare access are associated with frequent mental distress (FMD) in adults 65 years and older. Methods : Of the 123 427 study participants aged 65 years or older, 120 445 participants responded to the Behavioral Risk Factors Surveillance System (BRFSS) survey question on number of mentally unhealthy days. Participants who reported having 14 or more mentally unhealthy days during the past 30 days were considered as having FMD. Activity limitation, avoidance of medical care due to cost, and availability of personal doctor were examined for their association with FMD in multivariable logistic regression analysis. Age, sex, race/ethnicity, marital and employment status, emotional support, and life satisfaction were included as potential confounders. Results : The prevalence of FMD in this study population was 6.5% (95% CI = 6.3-6.8) with estimates significantly greater among women (7.2%, 95% CI = 6.9-7.6) as compared to men (5.5%, 95% CI = 5.1-6.0). The odds of FMD were more than 2-fold elevated for those who reported activity limitations due to physical, mental, or emotional problems (adjusted OR = 2.59, 95% CI = 2.33-2.87), and among those who reported health care cost as a barrier to see a doctor (adjusted OR = 2.14, 95% CI = 1.75-2.61). There was no significant relationship between availability of personal doctor and FMD observed in the study. Conclusions : The findings of this study showed that activity limitation and cost of medical care are associated with FMD in the US elderly population.